2022
DOI: 10.1021/acscentsci.2c01290
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Mesopore Confined Pt Nanoclusters Enable Unusual Self-Enhancing Catalysis

Abstract: As an important kind of emerging heterogeneous catalyst for sustainable chemical processes, supported metal cluster (SMC) catalysts have received great attention for their outstanding activity; however, the easy aggregation of metal clusters due to their migration along the substrate's surface usually deteriorates their activity and even causes catalyst failure during cycling. Herein, stable Pt nanoclusters (NCs, ∼1.06 nm) are homogeneously confined in the uniform spherical mesopores of mesoporous titania (mpT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…The loading facilitated the generation of interfacial active sites (Ti 3+ -O v -Pt δ+ ) during the reaction, thereby enhancing the cyclic catalytic activity. 24 If the porous material itself lacks catalytic activity, large pores can still facilitate the loading of catalytic substances, especially for large biomolecules such as enzymes. Guangshan Zhu and colleagues employed a strategy of synergistic assembly using multiple ligands to construct framework materials with large pores.…”
Section: Pore Structure Enhances Catalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The loading facilitated the generation of interfacial active sites (Ti 3+ -O v -Pt δ+ ) during the reaction, thereby enhancing the cyclic catalytic activity. 24 If the porous material itself lacks catalytic activity, large pores can still facilitate the loading of catalytic substances, especially for large biomolecules such as enzymes. Guangshan Zhu and colleagues employed a strategy of synergistic assembly using multiple ligands to construct framework materials with large pores.…”
Section: Pore Structure Enhances Catalytic Performancementioning
confidence: 99%
“…In addition, Prof. Yonghui Deng and Dongyuan Zhao reported that Pt clusters can be homogeneously confined in the uniform spherical mesopores of mesoporous TiO 2 , which is based on the interaction between Pt nanoclusters and metal oxide pore walls. The loading facilitated the generation of interfacial active sites (Ti 3+ -O v -Pt δ+ ) during the reaction, thereby enhancing the cyclic catalytic activity …”
Section: Pore Structure Enhances Catalytic Performancementioning
confidence: 99%
“…However, SMSI can also cause encapsulation of active metals by the reducible supports, limiting the exposure of interfacial sites and suppressing reaction activities. , Thus, constructing an MSI with suitable strength is crucial for maintaining catalytic activity and durability. In a recent issue of ACS Central Science , Deng, Wu, Zou, and co-workers reported a supported metal cluster catalyst Pt-mpTiO 2 with confined Pt nanoclusters . This catalyst design stabilizes the Pt nanoclusters and introduces a favorable medium MSI effect, providing a substantial amount of Ti 3+ -O v -Pt δ+ interfacial active sites and exhibiting superior catalytic performance compared to traditional Pt/TiO 2 catalysts.…”
mentioning
confidence: 99%
“…(F) Scheme of the mechanism and effect of increasing O v in used Pt-mpTiO 2 . Reproduced with permission from ref . Copyright 2022 The Authors.…”
mentioning
confidence: 99%
See 1 more Smart Citation